Investigation of the multicaloric properties in spark plasma sintered NiMnCoTi alloys - F. Villa; E. Villa; F. Passaretti; M. López-Cruz; J.L. Sánchez Llamazares (Journal of Materials Research and Technology)
Multicaloric Shape Memory Alloys (SMA) attract considerable scientific and technological interest nowadays as core materials for developing new solutions for solid-state cooling. The NiMnCoTi system is a ferromagnetic SMA that combines the caloric effect due to pseudoelastic deformation and magnetic field application. The efficiency of these two effects, related to grain structure for mechanical properties and induction of Thermoelastic Martensitic Transformation (TMT), is optimized by an appropriate microstructure. Therefore, among different preparation routes that may lead to defined shapes for practical use, Spark Plasma Sintering (SPS) is a promising preparation process. In this work, a Ni37.5Mn35Co12.5Ti15 (at. %) alloy, obtained by SPS is considered to investigate its multicaloric response base on the elastocaloric and magnetocaloric effects linked to the first-order martensitic-like structural transformation. Elastocaloric ΔTad of about 3.7 K for an uniaxial stress of 550 MPa and magnetocaloric ΔSmag of 19–22 J/kgK at 5 T are obtained. Moreover, new measurements of ΔTad with the elastic and magnetic field coupling are carried out. The application of the two fields simultaneously induces a significant ΔTad increase of about 36 %. The improvement of elastocaloric efficiency by magnetic field application was demonstrated at different strains values.